EFEKTIVITAS VIDEO ANIMASI DAN TEBAK GAMBAR TERHADAP PENGETAHUAN DAN SIKAP KONSUMSI BUAH DAN SAYURAN PADA ANAK TK: EFFECTIVENESS OF ANIMATED VIDEO AND IMAGING AGAINST LEARNING AND PERCEPTION OF CONSUMPTION OF FRUITS AND VEGETABLES IN PRESCHOOL CHILDREN - Febriandini, Isti Dwi Febriandini Dwi (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Nutrition education through animated video media and picture guessing is expected to improve knowledge and attitudes to consumption of fruit and vegetables in preschool children. This research aims to find out the results of nutrition education with animated video media and guess images and to know the results comparison or effectiveness of nutritional education between animated videos and guess pictures to knowledge and attitudes in preschool children in Beringin district of Purworejo. The study is a quasy experimental study using the pre-test and post-test method with control group design. The subjects of the study consisted of 30 Beringin high school students who were divided into two groups: 15 students in an animated video media group and 15 students of a picture guess group. Nutrition education on an animated video group and picture guessing was carried out for 90 minutes in Beringin district of Purworejo. The statistical tests used are Paired Samples Test and N-Gain Score. The results of this study showed that nutrition education using animated video media and image guess influenced the pre-test averages with post-test knowledge, with p-value values (p=0.014) using animation video media, and (p =0.000) using image guess media. And the resulting pre-angket p-values with post -angket attitudes were (p=0.003) using video animation media and(p=0.000) using picture guess medium. In this study, the use of animated video media was ineffective, while guess media was less effective in improving knowledge and attitudes to fruit and vegetable consumption in preschool children. Suggestions for delivery of educational material, more attention is paid to the duration of learning.